STRATEGI GURU DALAM MENGEMBANGKAN KEMAMPUAN LITERASI MEMBACA SISWA DI KELAS III SD/MI - Haq, Diniel; Rafidhah Hanum (Jurnal Ikhtibar Nusantara, 2026)
This study aims to describe the strategies used by teachers in developing reading literacy skills of third-grade students at MIN 3 Bireuen and to identify the supporting and inhibiting factors in its implementation. Reading literacy is an essential basic skill for elementary students because it supports understanding across all subjects. However, many students still experience difficulties in understanding reading texts, especially longer and more complex texts. This research used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving third-grade teachers, students, and the principal as research subjects. The results showed that teachers applied various strategies such as 15-minute reading habituation before lessons, read aloud, guided reading, group discussions, individual approaches, and the use of learning media such as Big Book and interesting reading materials relevant to students’ daily lives. Teachers also provided enrichment for high-achieving students and special guidance for students with reading difficulties. Supporting factors included parental involvement and school literacy programs, while inhibiting factors were low reading interest, limited attractive reading materials, and less optimal implementation of the School Literacy Movement. It can be concluded that varied, adaptive, and student-centered strategies are effective in improving students’ reading literacy skills.